Differential effects of oxytocin on mouse hippocampal oscillations in vitro. (14th October 2016) - Maier, Pia; Kaiser, Martin E.; Grinevich, Valery; Draguhn, Andreas; Both, Martin
Abstract: The hypothalamic neuropeptide oxytocin (OT) controls childbirth and lactation, is involved in social behaviors, plays a role in various psychiatric disorders, and has effects on learning and memory. Although behavioral effects of OT have been extensively studied, much less is known about its effects on neuronal and network activity patterns. Here, we investigate the effect of OT on two major patterns of hippocampal network activity in mouse hippocampal slices. We studied different in vitro models of gamma‐frequency oscillations and sharp wave‐ripple complexes (SPW‐R), two patterns implicated in spatial memory formation and memory consolidation respectively. Strikingly, we found a profound difference of OT on these distinct, mutually exclusive activity patterns. While gamma oscillations where not affected by the activation of hippocampal OT receptors, SPW‐R were potently and rapidly suppressed. Interestingly, the temporal precision of oscillation‐coupled spikes was enhanced at the same time. Thus, OT exerts strongly different modulatory effects on different network patterns, most likely by inhibition of different sets of inhibitory interneurons. The observed dichotomy between gamma and SPW‐R oscillations may have profound effects on the behavioral and cognitive effects of OT which are relevant to cognitive processes and to psychiatric diseases. Abstract : Oxytocin affects memory‐related hippocampal network oscillations differently. Sharp wave‐ripple complexes are strongly suppressed while gamma oscillations are not altered. This may have profound effects on behavioral and cognitive processes.